Pengaruh Kinerja Pegawai Terhadap Kepuasan Kerja Pegawai Dinas Perhubungan Kabupaten Raja Ampat - Fatimah, Husnul; Ambarini, Tri Kurniati; Dwi, Yuliani (LPPM IAIN Sorong, 2022)
This research aims to determine the effect of employee performance on job satisfaction of Raja Ampat Regency Transportation Service employees. The methods used are observation and literature study. This Field Experience Program (PPL) was carried out for two months, namely from 09 October to 09 December 2023. At that time we were assigned to the personnel section which had the task of managing all administration and documents for employees working at the Raja Regency Transportation Service Ampat. Based on the research results, it can be concluded that employee performance in the Transportation Service can have a significant impact on the success of the organization's mission